Burden and Predictors of Malnutrition Among Indian Adolescents (10–19 Years): Insights From Comprehensive National Nutrition Survey Data - Pandurangi, Raghavendra; Mummadi, Mahesh Kumar; Challa, Sairam; Reddy, N. Samarasimha; Kaliaperumal, Venkatesh; Khadar Babu, Chinta; Telikicherla, Usha Rani; Pullakandham, Raghu; Geddam, J. J. Babu; Hemalatha, Rajkumar (Frontiers in Public Health, 2022)
Introduction: Malnutrition among adolescents is a persistent problem with a profound impact on different dimensions of health. The objective of this analysis is to assess the burden of malnutrition (Stunting, Thinness, Overweight, and Obesity) and their associated socio-demographic factors among Indian adolescents (10-19 years) from the Comprehensive National Nutritional Survey (CNNS 2016-18) data. Methods: We used Individual-level data of 35,831 adolescents from the CNNS conducted in 2016-18 for this analysis. CNNS collected data on the nutritional status of adolescents along with socio-demographic variables from all states of India. Burden of stunting (Height for age Z score, HAZ < -2 SD), thinness (BMI for age Z score, BAZ < -2 SD), overweight (BAZ > 1 SD) and obesity (BAZ > 2 SD) were estimated for the entire country and individual states. A multivariable logistic regression analysis was used to assess the socio-demographic factors associated with stunting, thinness, and overweight. Results: CNNS collected data from 35,831 adolescents, of which 31,941 with BAZ scores, and 32,045 with HAZ scores were included in the final analysis. The burden of stunting and thinness among Indian adolescents was 27.4% (95% CI 26.4%, 28.4%) and 24.4% (23.5%, 25.4%) respectively. The burden of overweight and obesity was 4.8% (4.5%, 5.1%) and 1.1% (0.9%, 1.3%) respectively. Adolescents in the age group of 15-19 years (AOR 1.23, 95% CI 1.11, 1.36) compared to 10-14 years, females (AOR 1.20;1.08, 1.33) compared to males, were at increased odds of getting stunted. Adolescents from lowest wealth index families (AOR 1.66; 1.33, 2.07) were at increased odds of thinness compared to peers of higher wealth index families. Adolescents of 10-14 years (AOR 1.26, 95% CI 1.06, 1.49) compared to 15-19 years, urban residents (AOR 1.43, 95% CI 1.19, 1.71) compared to rural residents, were at increased odds of overweight. Conclusion: Indian adolescents face the double burden of malnutrition that is undernutrition (stunting and thinness) alongside overnutrition (overweight and obesity) that are linked with socio-demographic factors. The National Nutritional Programs (POSHAN Abhiyan) should prioritize high-risk groups specifically older age group (15-19 years), females, and low wealth Index quintile families identified in this analysis.